Effect of intoxication by gavage with pyrethroid and neonicotinoid insecticides on the liver in adult male rats of the Wistar strain. Issue 1 (31st December 2022) - Askri, Imen; Ben Lamine, Houda; Smiti, Raoudha; Tebourbi, Olfa; Hallegue, Dorsaf; Sakly, Mohsen; Ben Rhouma, Khémais
ABSTRACT: The use of pesticides has been widespread throughout the world. The intensive and uncontrolled use of these chemical substances has harmful effects on human health and the environment. Imidacloprid and Deltametrin are among the insecticides most commonly used. Our study evaluated the potential effects on hepatic function of Imidacloprid and Deltametrin in rats after subacute toxicity. Forty adult male Wistar rats were randomly divided into four groups of 10 rats each: the 1 st group was the control; the 2 nd group was exposed to Imidacloprid (25 mg/kg); the 3 rd group received Deltametrin (200 mg/kg) and the 4 th group received a mixture (Imidacloprid + Deltametrin) with the same dose for 30 days. The results showed that subacute exposure of rats to these insecticides induced a decrease in relative liver weights. On the other hand, hepatic activity was altered; however, there was a significant rise at the level of hepatic enzymes, blood sugar and lipids versus decreased protein in treated rats. These modifications were accompanied by alterations of the hepatic tissue structure in the treated rats, compared to the controls which remained intact. The alterations and lesions were more marked in the animals receiving the Imidacloprid and Deltametrin mixture. Subacute toxicity of Imidacloprid and Deltametrin, used individually or together, disturb liver function in rats and the treatment with the combination of the two worsens the condition.